A case of idiopathic acquired leukonychia totalis in a 17‐year‐old boy. Issue 2 (3rd February 2021) - Freeman, S. Caleb; Dick, Mary K.; Abid, Roshan; Tabatabai, Taylor M.; Berrebi, Kristen G.; Stone, Mary S.; Powers, Jennifer G.
Abstract: Whitening of the nail, or leukonychia, can have a wide range of etiologies including genetic disorders, trauma, poisoning, autoimmune disorders, and infections. Here we detail a case of idiopathic acquired leukonychia totalis in a 17‐year‐old boy. This condition has been reported 13 times in the literature previously, with only young boys being affected. Proper diagnosis may help minimize unnecessary investigations and prevent additional psychological stress over whether an underlying disease is present.